Tamoxifen-Dependent Induction of AGR2 Is Associated with Increased Aggressiveness of Endometrial Cancer Cells. (28th May 2017) - Hrstka, Roman; Podhorec, Jan; Nenutil, Rudolf; Sommerova, Lucia; Obacz, Joanna; Durech, Michal; Faktor, Jakub; Bouchal, Pavel; Skoupilova, Hana; Vojtesek, Borivoj
ABSTRACT: Tamoxifen treatment in breast cancer patients is associated with increased risk of endometrial malignancies. Significantly, higher AGR2 expression was found in endometrial cancers that developed in women previously treated with tamoxifen compared to those who had not been exposed to tamoxifen. An association of elevated AGR2 level with myometrial invasion occurrence and invasion depth was also found. In vitro analyses identified a stimulatory effect of AGR2 on cellular proliferation. Although adverse tamoxifen effects on endometrial cells remain elusive, our work identifies elevated AGR2 as a candidate tamoxifen-dependent mechanism of action responsible for increased incidence of endometrial cancer.